Kepemimpinan, Insentif dan Pelatihan Terhadap Kinerja Karyawan Pada Kantor Bank Syariah Mandiri Cabang Pematang Siantar - Sugeng Sukoco; Satria Tirtayasa; Hazmanan Khair Pasaribu (Universitas Pendidikan Nasional, 2020)
ABSTRACTThe purpose of this research is to know the leadership, incentives and training on the performance of employees at Bank Syariah Mandiri Pematangsiantar Branch. The population in this study is the population in this study is the employees who are in the office of Bank Syariah Mandiri Pematangsiantar Branch as much as 40 people.. The sample is used as many as 40 employees in Bank Syariah Mandiri Office, Pematangsiantar, amounting to 40 people. The data collection techniques in this study are documentation and poll list. Data analysis techniques using multiple linear regression analyses, classical assumption Test T, Test f and coefficient of determination. Data processing in this study uses the program SPSS 22.00 for Windows Software. Based on the results of the research conducted, the partial leadership testing has significant effect on employee performance. Incentive partial testing has significant effect on employee performance. Training partial testing has significant effect on employee performance. Simultaneous testing of leadership influences, incentives and training significantly affects employee performance.